Sur la poésie religieuse (en occitan) : de Jean-Baptiste Séguy à Robert Lafont (1964) - Philippe Gardy (Revue des Langues Romanes)
An internationally renowned sociologist of religions, Jean Séguy (1925-2007), under the name of Jean-Baptiste Séguy (or Seguin in Occitan), also devoted himself for many years to Occitan language and culture, eventually becoming a writer (poet, prose-writer, critic) in this language. From his extensive correspondence with the academic and writer of Occitan Robert Lafont (1923-2009), we comment here on the main passages of a long letter (1964) in which he explains what poetry, Occitan poetry and religious poetry in particular mean to him.